Ireland : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper analyzes budgetary developments in Ireland during the 1990s. The paper highlights that Irish fiscal policy has been central to the social consensus on macroeconomic policies. The economic buoyancy has reinforced this cycle by facilitating the tax cuts and increases in social spending that have been instrumental to the social consensus on policies, while also helping to keep deficits low. The paper also discusses the participation of Ireland in the European Monetary Union.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Factor Income Distribution